A mRNA Vaccine Encoding for a RBD 60-mer Nanoparticle Elicits Neutralizing Antibodies and Protective Immunity Against the SARS-CoV-2 Delta Variant in Transgenic K18-hACE2 Mice - Brandys, Pascal; Montagutelli, Xavier; Merenkova, Irena; Barut, Güliz T.; Thiel, Volker; Schork, Nicholas J.; Trüeb, Bettina; Conquet, Laurine; Deng, Aihua; Antanasijevic, Aleksandar; Lee, Hyun-Ku; Valière, Martine; et al. (Frontiers in Immunology, 2022)
Two years into the COVID-19 pandemic there is still a need for vaccines to effectively control the spread of novel SARS-CoV-2 variants and associated cases of severe disease. Here we report a messenger RNA vaccine directly encoding for a nanoparticle displaying 60 receptor binding domains (RBDs) of SARS-CoV-2 that acts as a highly effective antigen. A construct encoding the RBD of the delta variant elicits robust neutralizing antibody response with neutralizing titers an order of magnitude above currently approved mRNA vaccines. The construct also provides protective immunity against the delta variant in a widely used transgenic mouse model. We ultimately find that the proposed mRNA RBD nanoparticle-based vaccine provides a flexible platform for rapid development and will likely be of great value in combatting current and future SARS-CoV-2 variants of concern.